The Influence of Environmental Costs and Company Size on The Level of Corporate Social Responsibility (CSR) - Heri Anggraini; Harsi Romli; Vhika Meiriasari (ProBisnis : Jurnal Manajemen, 2023)
This study aims to examine the effect of environmental costs and company size on the level of Corporate Social Responsibility (CSR). Environmental costs are measured using cost divided by profit, company size using the natural logarithm (Ln) of total assets, and Corporate Social Responsibility (CSR) is measured using the number of items disclosed by the company divided by the number of items that should be disclosed by the company. This type of research is quantitative. The population in this study are all mining companies listed on the Indonesia Stock Exchange (IDX) with an observation period starting from 2019 to 2021. The sampling technique used is the purposive sampling method, in order to obtain a total of 22 mining companies that have met the specified criteria. has been established. The data source used is secondary data in the form of annual reports obtained from www.idx.co.id. In this study, data analysis techniques used the SPSS (Statistical Package for Social Science) 26 software application. The results showed that environmental costs had a significant effect on the level of Corporate Social Responsibility (CSR). And company size has a significant effect on the level of Corporate Social Responsibility (CSR).